High-Sensitive Surface Plasmon Resonance Imaging Biosensor Based on Dual-Wavelength Differential Method - Zeng, Youjun; Zhou, Jie; Sang, Wei; Kong, Weifu; Qu, Junle; Ho, Ho-Pui; Zhou, Kaiming; Gao, Bruce Zhi; Chen, Jiajie; Shao, Yonghong (Frontiers in Chemistry, 2021)
Intensity interrogation surface plasmon resonance (ISPR) sensing has a simple schematic design and is the most widely used surface plasmon resonance technology at present. However, it has relatively low sensitivity, especially for ISPR imaging (ISPRi). In this paper, a new technique for the real-time monitoring of biomolecule binding on sensor surfaces via ISPRi detection is described. The technique is based on the interrogation of the differential value of two intensities at two specific wavelengths from the reflected light spectrum. In addition, we also optimized the selection of dual-wavelength parameters under different circumstances to achieve the highest sensitivity. The new technique achieved a refractive index resolution (RIR) of 2.24 × 10–6 RIU, which is far beyond that of traditional ISPRi technique. Moreover, our new ISPRi technique also realized the real-time detection of high-throughput biomolecular binding. This study is expected to promote the development of faster and more accurate SPRi technologies.